Strategies for managing postmenopausal bleeding: a clinician's perspective - Gupta, Sumedha; Kalwaniya, Dheer Singh (International Journal of Research in Medical Sciences, 2024)
Postmenopausal bleeding (PMB) poses a diagnostic challenge due to the varied presentation of endometrial pathologies ranging from benign endometrial atrophy to the possibility of endometrial carcinoma. Although the incidence varies with patient characteristics, it warrants thorough evaluation. Risk factors such as obesity and hormone use should guide assessment. Bleeding may originate from various gynecological and non-gynecological sites, demanding meticulous history-taking and examination. Transvaginal sonography (TVS) is typically the initial step, yet its accuracy in excluding carcinoma remains debated. Invasive procedures like hysteroscopy and endometrial sampling offer higher accuracy but are more intrusive. The optimal diagnostic strategy remains uncertain, necessitating focused research for enhanced accuracy. TVS-guided assessment with an endometrial thickness (ET) threshold of >4 mm prompts evaluation and endometrial sampling. Progestogen therapy mitigates endometrial cancer risk associated with estrogen use, with atypia-hyperplasia necessitating vigilant monitoring and possible hysterectomy. Patient counselling on treatment options is crucial. In summary, PMB warrants a systematic approach integrating imaging, histological assessment, and tailored therapy guided by risk factors, final diagnosis and patient preferences.